Uterine Rupture During Labor in a Patient that Had Undergone Repetitive Uncomplicated Hysteroscopic Metroplasty - Bülent Haydardedeoğlu; Seda Yüksel; Ayşe Parlakgümüş; Esra Kılıçdağ; Tayfun Bağış (Medical Network, 2011)
Hysteroscopic surgery when performed by a well-trained hysteroscopic surgeon is a safe procedure with an overall complication rate of 3%, and the complications comprise uterine perforation, excessive hemorrhage, air embolus, pulmonary edema, excessive glycine absorption, and infection. After hysteroscopic septum resection, a remnant uterine septum might be visualized on control hysterosalpingography or control hysteroscopy. Kormanyos et al. observed a remnant uterine septum in 38% of patients after initial hysteroscopic metroplasty. In our case hysteroscopy was performed twice without complications. We used two different techniques in the same patient; the first involved a resectoscope with a unipolar electrode and the second involved a Versapoint with a bipolar electrode. Although these two operation types appear to be similar, hysteroscopic metroplasty with Versapoint is a safe and effective alternative to the operative resectoscope. Our case demonstrates a rare but dramatic complication of hysteroscopic metroplasty. Uterine perforation during hysteroscopic metroplasty is accepted as a risk factor for uterine rupture in pregnancy. The extensive enlargement of the uterus during pregnancy might be a reasonable cause of uterine rupture in patients that have undergone hysteroscopic metroplasty previously.